Dust deposition and its significance to soil nutrients in the Otindag Desert, China. (November 2021) - Wang, Xunming; Cai, Diwen; Li, Danfeng; Lou, Junpeng; Zheng, Yang; Hu, Shi; Liu, Fa
Abstract: Quantification of fine fraction and nutrient inputs by dust deposition is vital to understand the biogeochemical cycling and its effect on vegetation succession in arid and semiarid regions. The Otindag Desert of China is usually regarded as a dust source area, and little is known about its sink function by dust deposition. Dust and topsoil sampling and nutrient analyses were conducted to determine the contributions of dust deposition (fractions <50 μm in diameter) on topsoil heterogeneity across the Otindag Desert. Mean dust deposition intensity from field investigation was 19.69 ± 7.77 g/m 2 from August 2018 to July 2019. There were significant spatial differences in dust deposition, and the Otindag Desert received more dust deposition from external sources. Inputs of available phosphorus, total phosphorus, total nitrogen and soil organic carbon were 0.45 ± 0.083 mg/m 2, 0.011 ± 0.007 g/m 2, 0.027 ± 0.018 g/m 2, and 0.331 ± 0.224 g/m 2, respectively. The nutrient contents within dust deposition fractions were higher on average by 104% than topsoil, and the cooccurrence of dust emission and deposition contributes to the heterogeneity of topsoil. The results of this study are essential for taking efficient measures to restore degraded land in the Otindag Desert and other similar regions. Highlights: Dust deposition is 19.69 g/m 2 in the Otindag Desert from August 2018 to July 2019. The amount of dust deposition is higher than that of dust loss during the period. Dust deposition brings more nutrients to the topsoil during the period. Dust deposition may affect vegetation community evolution in the Otindag Desert.